Extraction of iodine-131 (i-131) by synthetic and natural antibacterial carbon adsorbents for clinical nuclear medicine waste management - Sunaiwi, Rosidah (2023)
Patients undergoing high-dose radioiodine ablation (RAI) therapy need to be isolated in the specially designed ward at the nuclear medicine department (Lian, 2013). Thus, excreta from those patients are considered radioactive waste. A large amount of radioactive sewage is produced as more high-activity radionuclide therapy is implemented. The radioactive wastewater had to be stored in a delay tank until the radioactivity decayed below the legally established acceptable limit (<1.2μ Ci/L) before being discharged into the public sewer (IAEA, 2000). A delay tank indirectly limits the number of patient admissions due to its limited volume size and periodical clearance. Thus, this study's purpose is to propose an alternative antibacterial adsorbent for I-131 extraction from clinical radioactive wastewater at the nuclear medicine department by using graphene oxide/silver (GOAg), and bamboo activated carbon (BAC), environmentally friendly carbon-based adsorbent materials and serve as synthetic and natural antibacterial carbon adsorbent. Radioactive clinical wastewater samples from a delay tank are mixed with adsorbents at concentrations 1, 2, 3, 4 and 5 mg/ml before being filtered using a membrane filter. The percentage of decay rate for both carbon-based materials at 5 mg/ml was significantly higher than any concentrations which is 84.05% for GOAg:I-131 and 77.78% for BAC:I-131. The synthesized carbon-based materials and its sediments formed on the membrane filter were analyzed using; FESEM for morphological analysis; XPS spectrum for C1s of adsorbents show intensity peaks of: (a) C=C and C–C for GOAg and its sediments; (b) C–C, C=O and π–π* transitions for BAC and its sediments; FTIR spectra revealed various functional groups of adsorbents; (a) C=C, C=O and C–O–C for GOAg and its sediments; (b) C=C, C–C and C–O for BAC and its sediments; crystalline of adsorbents analyzed using XRD, the XRD pattern exhibit peaks at 2θ value that attributed to: (a) (002) diffraction plane, (220) crystallographic plane, (111) plane of Ag2O and (200) crystallographic plane in GOAg and its sediments; (b) (002) and (100) plane in BAC and its sediments. Estimation of remaining beta particles during the decontamination of I-131 was carried out using PHITS. The finding of this study can indicate the potential for the innovation of replaceable adsorbent material and filtration for radionuclide extractions from radioactive wastewater in nuclear medicine services. Furthermore, it can also serve as an alternative solution to increase the admission limit for existing patients at Hospital Universiti Sains Malaysia, Kubang Kerian, Kelantan.